Mapping lichen changes in the summer range of the George River Caribou Herd (Québec-Labrador, Canada) using Landsat imagery (1976-1998) - Théau, Jérôme; Duguay, Claude R. (Rangifer, 2004)
Habitat studies are essential in order to understand the dynamics of migratory caribou herds and to better define management strategies. In this paper, multi-date Landsat images are used to map lichen in the summer range of the George River Caribou Herd (GRCH), Québec-Labrador (Canada), over the period from 1976 to 1998. Multi-Spectral Scanner scenes from the seventies and Thematic Mapper scenes from the eighties and nineties were radiometrically normalized and processed using spectral mixture analysis to produce lichen fraction maps and lichen change maps. Field sites, surveyed during summer campaigns in 2000 and 2001, are used to validate the lichen maps. Results show a good agreement between field data and the lichen results obtained from image analysis. Maps are then interpreted in the context of previous caribou dynamics and habitat studies conducted in the study area over the last three decades. The remote-sensing results confirm the habitat degradation and herd distribution patterns described by other investigators. The period between 1976-1979 and 1985-1986 is characterized by a localized decrease in lichen cover in the southern part of the study area, whereas from 1985-1986 to 1998 the decrease in lichen cover extends northward and westward. This period coincides with the widest extent of the GRCH summer range and activity. The approach presented in this paper provides a valuable means for better understanding the spatio-temporal relation between herd dynamics and distribution, as well as habitat use. Satellite remote sensing imagery is a useful data source, providing timely information over vast and remote territories where caribou populations cannot be surveyed and managed on a frequent basis.